The Influence of STAD Learning Model, Think Pair Share and Conventional Learning - Yuliani, Yuliani; Susilawati, Wati; Malik, Adam (Abdurrauf Journal of Islamic Studies, 2024)
This study aims to describe the effect of the application of STAD, TPS and Conventional learning models on students' Critical Thinking Skills, the effect of the application of STAD, TPS and Conventional learning models on students' Critical Thinking Skills based on students' school origin, find out whether there is an interaction between the Learning Model and School Origin in determining the Critical Thinking Skills Score Students in PAI subjects. This study uses a quantitative approach with a quasi-experimental method and technical data analysis using a two-track ANOVA analysis using the SPSS application. The sample taken was 61 students from SMK Pertiwi Sukamandi class X TBSM. The results of this study show that there are differences in students' Critical Thinking Skills in PAI subjects based on learning models (STAD, TPS and Konv), there are no differences in students' Critical Thinking Skills in PAI subjects based on school origin (SMP and MTS); there is no interaction between Learning Models and School Origin in determining Critical Thinking Skills students in PAI subjects. Penelitian ini bertujuan untuk mendeskripsikan pengaruh penerpan model pembelajaran STAD, TPS dan Konvensional terhadap Critical Thinking Skills siswa, pengaruh penerpan model pembelajaran STAD, TPS dan Konvensional terhadap Critical Thinking Skills siswa berdasarkan asal sekolah siswa, mengetahui apakah terdapat interaksi antara Model Pembelajaran dan Asal Sekolah dalam menentukan Skor Critical Thinking Skills Siswa Pada Mata Pelajaran PAI. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi eksperimen dan teknis analisis data menggunakan analisis ANOVA dua jalur dengan menggunakan aplikasi SPSS. Sampel yang diambil sebanyak 61 siswa dari sekolah SMK Pertiwi Sukamandi kelas X TBSM. Hasil dari penelitian ini menunjukan bahwa terdapat perbedaan Critical Thinking Skills siswa pada mata Pelajaran PAI berdasarkan model pembelajaran (STAD, TPS dan Konv), tidak terdapat perbedaan Critical Thinking Skills siswa pada mata Pelajaran PAI berdasarkan Asal sekolah (SMP dan MTS); tidak terdapat interaksi antara Model Pembelajaran dan Asal Sekolah dalam menentukan Critical Thinking Skills siswa pada mata Pelajaran PAI